Imagination and medical education. Issue 1 (1st June 2001) - Evans, Donald
Abstract : Rival and apparently exclusive views have been canvassed about the instrumental use of the humanities in medical education. The novel is seen as offering exemplifications of moral principles on the one hand, whilst on the other such an approach is said to miss the essence of reading a novel by misrepresenting the engagment of the reader. The use of the humanities in medicine as a stimulus to reflective practice is presented as a preferable account which recognises that there is truth in each of the former views.